A note on local asymptotic behaviour for Brownian motion in Banach spaces - Mou-Hsiung Chang (International Journal of Mathematics and Mathematical Sciences)
In this paper we obtain an integral characterization of a two-sided upper function for Brownian motion in a real separable Banach space. This characterization generalizes that of Jain and Taylor [2] where B=ℝn. The integral test obtained involves the index of a mean zero Gaussian measure on the Banach space, which is due to Kuelbs [3]. The special case that when B is itself a real separable Hilbert space is also illustrated.